IMPLEMENTASI SISTEM PENILAIAN KINERJA KARYAWAN DENGAN METODE FUZZY SIMPLE ADDITIVE WEIGHTED - Krisnadhi Hariyanto; Eko Budi Satoto (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2014)
The performance of some companies is very important for tje evaluation of and planning for thefuture. The employees should be conducted to determine the one who will be every employee. Inpractice, this assessment on work performance of employees to do with methods good and right, soas not to be errors in judgmnet. The assessment conducted to be able to ensure fair threatment andbe satisfactory for them is, and eventually grow loyalty his work. Fuzzy additive weighting simplemethod chosen to conduct the assessment and ranking work performance of employees. From theresults of the tests may conclude that it can implement a work contract to the employees of thecompany. Surya Mas Megah Steel.